La presunción judicial como medio de prueba en el ordenamiento jurídico ecuatoriano - Gabriela Pamela, Zurita Mora (2021)
ABSTRACT This investigative work proposes to carry out a study and analysis of the judicial presumption as a means of evidence and its incidence in resolving causes that regulate in the General Organic Code of Processes, taking into account the flaw at the normative level that Art. 172 represents the COGEP, norm that results as a speculative method to resolve litigation in which there are not sufficient probative means to convince the judge of the facts. This legal figure significantly impacts the judges' decisions since it allows the judge to reason presumptively and assess the evidence through his experience, legal technique, and reasonable criticism. To have the conviction of the facts expressed by the procedural parties. This investigative work represents the consequence of legal research carried out through investigative methods, research techniques, and instruments to study this legal figure from a normative, doctrinal and critical perspective. This research has made it possible to highlight the problem raised. Keywords: judicial presumption, evidence, direct evidence, indirect evidence, reasonable criticism. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980